2003
DOI: 10.5194/angeo-21-1773-2003
|View full text |Cite
|
Sign up to set email alerts
|

Modeling transverse heating and outflow of ionospheric ions from the dayside cusp/cleft. 2 Applications

Abstract: Abstract. In this paper, we consider major ion energization mechanisms in the dayside cusp/cleft region. This includes transverse ion heating by ion cyclotron resonance (ICR), ion energization through structures of field-aligned electric potential drops, and transverse heating by lower hybrid (LH) waves. First, we present and discuss three typical cusp/cleft crossings associated with one of the first two mechanisms mentioned above. Then, we develop a procedure for finding the altitude dependence of ICR heating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 60 publications
4
31
0
Order By: Relevance
“…Heating over extended altitude intervals as reported in Bouhram et al (2003b) is essentially consistent with the observations, as further indicated by the simple estimate we performed according to the scheme described in Sect. 3.5.…”
Section: Structure Of Outflowing Ions and Of The Source Regionsupporting
confidence: 76%
See 1 more Smart Citation
“…Heating over extended altitude intervals as reported in Bouhram et al (2003b) is essentially consistent with the observations, as further indicated by the simple estimate we performed according to the scheme described in Sect. 3.5.…”
Section: Structure Of Outflowing Ions and Of The Source Regionsupporting
confidence: 76%
“…The energies reported in the above cited papers tend to increase with observation altitude, consistent with heating over extended altitude intervals, as inferred by Miyake et al (1993); Bouhram et al (2003b). However, it is an important question as to how much further energization takes place at high altitude.…”
Section: Introductionsupporting
confidence: 50%
“…They combined oxygen data from the Akebono, Interball-2, and Cluster satellites and followed the global development of the energetic (up to ∼10 keV) ion outflow over a continuous and broad altitude range up to about 5.5 R E . They confirmed the results of Bouhram et al (2003b), such as the fact that transverse ion heating in the cusp/cleft is height-integrated at radial distance below 4 R E . The results inferred from Cluster observations put forward evidence of a saturation of both a transverse energization rate and ion gyroradii.…”
Section: Introductionsupporting
confidence: 77%
“…They found that any triplet of (residence time of the ions when being energized, α, and ω 0 ) leads to a unique transport pattern feature of ion flows associated with a cusp/cleft ionospheric source. Bouhram et al (2003b) used high-altitude (1.5-3 R E ) ion observation as constraints and the results of Bouhram et al (2003a) are used to determine the altitude dependence of transverse ion heating during a significant number of the Interball-2 satellites. Bouhram et al (2004) focused on the altitude dependence of oxygen ion conics in the dayside cusp/cleft region.…”
Section: Introductionmentioning
confidence: 99%
“…The ions have seldom experienced the heating for as long as is assumed by the theory at the time of observation. Some of the most intense heating is known to occur in a very limited region at the equatorward side of the cusp, sometimes called the "cusp heating wall" (Bouhram et al, 2003), possibly caused by a combination of waves and quasi-static electric fields (Lindstedt et al, 2010). This could provide O + ions with energies of several keV.…”
Section: Discussionmentioning
confidence: 99%